Tariff spillovers and new rules for multilateral tariff negotiations - Eddy Bekkers; Alexander Keck (World Trade Organization (WTO), 2024)
Some countries have voiced unease about differences between their own tariff rates and those of major trading partners, calling for more "reciprocity". These calls raise the question how large the negative spillover effects of countries' tariffs on others have become over time. Given a presumed sense of "reciprocity" at the end of the Uruguay Round and for subsequent WTO accessions, an important question for the future of multilateral trade negotiations may be how cross-cutting formulae or "rules" could be developed that might address such spillovers. In this paper we (i) analyze the spillover effects of tariffs and (ii) explore possible tariff liberalization rules and their economic effects, employing the WTO Global Trade Model. We measure the spillover effects of tariffs by the export or terms of trade losses incurred by trading partners. The analysis shows that there are large differences in the per capita spillover effects of tariff rates and that about 70% of the spillover effects can be explained by initial tariff rates, the share in global imports, population, and a product's trade elasticity. Five possible tariff liberalization rules are introduced, with the fifth one being based on the determinants of the negative spillover effects on other countries. Simulating the tariff liberalization rules shows that they would address such spillovers to different extents and lead to global export increases of about 3%, with increases of more than 20% for some countries. Real income effects are positive in most regions, although welfare does not increase in all regions because of negative terms of trade effects. Under the fifth rule, real income and terms of trade effects are related to the adverse spillover effects imposed in other countries, i.e. regions generating larger adverse spillover effects benefit from smaller real income gains or incur larger real income losses. However, this relation is not perfect, suggesting that flexibility may be needed in the implementation of the rule.
Keywords: F14; 330; Tariff negotiations; reciprocity; terms of trade effects; CGE-modelling